2018
DOI: 10.3390/molecules23123182
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved Spectroscopic Study of N,N-Di(4-bromo)nitrenium Ions in Selected Solutions

Abstract: Nitrenium ions are important reactive intermediates in chemistry and biology. In this work, femtosecond and nanosecond transient absorption (fs-TA and ns-TA) along with nanosecond time-resolved resonance Raman (ns-TR3) experiments were employed to examine the photochemical pathways of N-(4,4′-dibromodiphenylamino)-2,4,6-trimethylpyridinium BF4− (salt (DN) from just absorption of a photon of light to the production of the important N,N-di(4-bromophenyl)nitrenium ion 2. In acetonitrile (MeCN), the formation of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…The singlet ground state properties of the DN was also demonstrated by the nanosecond time-resolved resonance Raman (ns-TR 3 ) spectroscopy data, in which the direct fingerprint information of DN was obtained. Similar reaction mechanisms to those found in Falvey and coworkers’ previous study were also concluded in the near-neutral aqueous solution, as found by a vibrational spectroscopic study [15].…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…The singlet ground state properties of the DN was also demonstrated by the nanosecond time-resolved resonance Raman (ns-TR 3 ) spectroscopy data, in which the direct fingerprint information of DN was obtained. Similar reaction mechanisms to those found in Falvey and coworkers’ previous study were also concluded in the near-neutral aqueous solution, as found by a vibrational spectroscopic study [15].…”
Section: Introductionsupporting
confidence: 88%
“…Additionally, Thomas and coworkers reported that the N,N –di(4–bromophenyl)nitrenium ion ( DN ) formed after photoexcitation of the N –(4,4′–dibromodiphenylamino)–2,4,6–trimethylpyridinium BF 4 - salt ( 1 ) showed more stability and a much longer lifetime than the unsubstituted N,N –diphenylnitrenium ion, the lifetime of which was 124 µs in neat MeCN solution and 6.57 µs in an aqueous solution [13]. Furthermore, our group has determined that the generation of DN both in MeCN and near neutral aqueous solution was around 4 ps [15]. The singlet ground state properties of the DN was also demonstrated by the nanosecond time-resolved resonance Raman (ns-TR 3 ) spectroscopy data, in which the direct fingerprint information of DN was obtained.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fs-TA and ns-TA experiments here utilized the same experimental apparatus and methods that have been detailed in previous work [ 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies 10,12 demonstrated that N,N-di (4-bromophenyl) for >500 μs in water and does not react at an observable rate with any added nucleophiles. These experiments support the original assignment of the 720 nm signal to the radical cation, rather than the nitrenium dication.…”
Section: Introductionmentioning
confidence: 99%